SUPPRESSION ABILITY OF CRUDE EXTRACT DERIVED FROM MARINE BIOTA AGAINST FUSARIUM OXYSPORUM F.SP. VANILLAE - Suada, I Ketut; Suniti, Ni Wayan (Jurnal Biologi Udayana; Vol 14 No 1 (2010): Jurnal Biologi, 2010)
The objective of this research was to investigate suppression ability of marine biota extracts against Fusarium oxysporum f.sp. vanillae of vanilla stem rot. Samples were collected at intertidal zones and in the depth of 1-7 m from seven beaches in Bali. Screening of active compounds of biota extracts were conducted using inhibition zone of well diffusion method on Potato Dextrose Agar (PDA). The extract was tested in-vitro in PDA medium using completely randomized design with three replicates. The methanolic extract of Aglaophenia sp. was able to suppress the growth of F. oxysporum f.sp. vanillae effectively, with minimum inhibition concentration (MIC) of 0.05 %. The extract inhibited colony growth diameter and total mycelial dry weight.
Keywords: Fusarium oxysporum f.sp, vanillae, Aglaophenia sp., well diffusion method